Ship-mediated Marine Bioinvasions: Need for a Comprehensive Global Action Plan - Arga Chandrasekar Anil; Venkat Krishnamurthy (ASEAN Journal on Science and Technology for Development, 2018)
Concern for marine bioinvasion has drawn international attention. The action plans in place to address this issue and those that are being promulgated are in need of a reassessment. A review of invertebrate invasions across the world indicates inter-linkages between vectors. In this paper an effort is made to illustrate the geographical spread of invasive invertebrate organisms from different bioregions and the possible causes for their success. Shipping, which is the major vector identified for the success of marine bioinvasion, needs to be addressed in tandem with domestic, intra- and inter-regional precautionary measures, as prevention is the only cure.